Pengaruh Product Perceived Quality Dan Citra Toko Terhadap Minat Beli Produk Label Pribadi Indomaret Tanah Grogot - Anang Antin; Rasyidi Rasyidi; Maryono Maryono (Universitas Lambung Mangkurat, 2016)
The test results prove that the quality of care as measured by the variable aspects of physical evidence (X1), reliability (X2), responsiveness (X3) and guarantees (X4), which is partially the result of data processing with the use of t-test found that the number t for physical evidence variable (X1) is 2.708, the reliability (X2) is 4.784, responsiveness (X3) of 4.456 and a guarantee (X4) of 5,600 and while the table t of 1.98 or known than the t count> t table it can be concluded that there is a fourth partial effect of these variables on customer satisfaction. For empathy variable (X5) at 0,523 t, while t table when compared to the 1.98 or t <t table it can be concluded that there is no significant effect on satisfaction pelanggan.hal is also the reason why no significant effect of empathy variable partial to customer satisfaction. While simultaneously there is a significant influence on customer satisfaction Regional Water Company Kapuas of 0698 or 6.98% and the remaining 30.2% is influenced by other variables not examinet in this study. Keywords: Service Quality, Customer Satisfaction